Serum Uric Acid Level Among Children with Familial Mediterranean Fever - Huda Marzouk; Shimaa Atef; Mariam Mohamed El-Khity; Hend Mohamed Abu Shady (Cairo University, Faculty of Medicine, Department of Pediatrics, 2024)
Background: Familial Mediterranean fever (FMF) is the most frequent form of inherited periodic fever syndromes. It is caused by a mutation in the MEFV gene and is transmitted by autosomal recessive mode. It is marked by recurring fever episodes with a range of symptoms due to inflammation in the pleura, synovium, and peritoneum. In FMF patients, subclinical inflammation frequently persists throughout the attack-free periods. Uric acid is a product of purine nucleotides catabolism. It is elevated in tissue damage. Aim of the work: To assess uric acid levels and glomerular filtration rate (GFR) in children with FMF during the attack-free period. Subjects and Methods: This cross-sectional study assessed uric acid levels and GFR in 40 children with FMF during the attack-free period. They were enrolled from the Pediatric Rheumatology Outpatient Clinic, Children's Hospital, Faculty of Medicine, Cairo University. Their uric acid levels were compared to a control group of 40 healthy age and sex-matched children. Results: The mean ± SD age of FMF patients was 12.65 ± 1.82 years and 50% were males while thecontrolgroupmeanagewas12.6±1.82years(p=0.903)and52.5%weremales(p=0.823). The mean± SD GFR among FMF patients was 124.75 ± 43.91(ml/min/1.73m2), while among the control group it was 155.48 ± 63.17 ml/min/1.73m2 (p =0.054). Seven (17.5%) FMF patients had reduced GFR (mean ± SD = 84.29± 3.15 ml/min/1.73m2). The mean ± SD uric acid folds of upper level of normal was 0.55 ± 0.13 among the control group, 0.75±0.21in the FMF group, 0.49 ± 0.21 among those with normal GFR and 0.74 ± 0.21 among those with reduced GFR respectively (p=0.286). Three (7.5%) of the FMF patients had microalbuminuria and normal GFR. Conclusion: Uric acid levels were within normal range for age among children with FMF during the attack-free periods and were not predicative of impaired GFR or presence of albuminuria. In a subset of FMF patients, GFR was impaired and others had microalbuminuria during the attack-free periods despite having normal kidney functions. More studies are needed to highlight the risk factors and value of GFR and microalbuminuria in follow up of children with FMF. SUA levels were not elevated in children with FMF during the attack-free period.